Characterization and use of HapT1-derived homologous tumors as a preclinical model to evaluate therapeutic efficacy of drugs against pancreatic tumor desmoplasia - Suklabaidya, Sujit; Das, Biswajit; Ali, Syed Azmal; Jain, Sumeet; Swaminathan, Sharada; Mohanty, Ashok K.; Panda, Susen K.; Dash, Pujarini; Chakraborty, Subhankar; Batra, Surinder K.; Senapati, Shantibhusan (Oncotarget, 2016)
Desmoplasia in human pancreatic cancer (PC) promotes cancer progression and hinders effective drug delivery. The objectives of this study were to characterize a homologous orthotopic model of PC in Syrian golden hamster and investigate the effect of anti-fibrotic (pirfenidone), antioxidant (N-acetyl cysteine, NAC) and anti-addiction (disulfiram, DSF) drugs on desmoplasia and tumor growth in this model. The HapT1 PC cells when implanted orthotopically into hamsters formed tumors with morphological, cellular and molecular similarities to human PC. Protein profiling of activated hamster pancreatic stellate cells (ha-PSCs) revealed expression of proteins involved in fibrosis, cancer cells growth and metastasis. Pirfenidone, suppressed growth of HapT1 cells and the desmoplastic response in vivo; these effects were enhanced by co-administration of NAC. Disulfiram alone or in combination with copper (Cu) was toxic to HapT1 cells and PSCs in vitro; but co-administration of DSF and Cu accelerated growth of HapT1 cells in vivo. Moreover, DSF had no effect on tumor-associated desmoplasia. Overall, this study identifies HapT1-derived orthotopic tumors as a useful model to study desmoplasia and tumor-directed therapeutics in PC. Pirfenidone in combination with NAC could be a novel combination therapy for PC and warrants investigation in human subjects.